The transfR toolbox for transferring observed streamflow series to ungauged basins based on their hydrogeomorphology. (January 2023) - de Lavenne, Alban; Loree, Tom; Squividant, Hervé; Cudennec, Christophe
Abstract: This R package technically gathers the methods developed and lessons learnt over recent years for estimating discharge of ungauged outlets, in a runoff–runoff type approach (discharge is both the input and output). It uses the observed discharge of neighbouring gauged basins and a geomorphology-based deconvolution–convolution modelling approach. The continuous hydrological modelling is based on the description of the hydro-geomorphometry of the river drainage network that can be easily described for any outlet considered. An inversion of this model allows us to deconvolute the observed discharge series and to estimate the signal of the water flowing into rivers from the hillslope, namely the net rainfall. The transfer of this net rainfall to a targeted ungauged basin enables the simulation of the discharge series there. The methodology has been tested in several hydro-climatic contexts, and with this package we aim to encourage further evaluation and improvement as well as subsequent operational applications. Highlights: transfR is a R package designed for discharge prediction in ungauged basins. Geomorphology-based hydrological transfer functions across river network are built. Inverse modelling facilitates spatial interpolation of discharge observations.